TAREKAT QADIRIYAH WA NAQSABANDIYAH TERHADAP KESALEHAN SOSIAL MASYARAKAT DUSUN GEMUTRI SUKOHARJO SLEMAN - Siswoyo Aris Munandar; Sigit Susanto; Wahyu Nugroho (LP2M IAIN Palangka Raya, 2020)
This study was based on a case study on the era challenges that began to erode spiritual and social aspects of the society. Sufism through thariqah offers an increase in morality /ethics. Thariqah was believed as one of media for social change in boosting morality / ethics. The main reason that thariqah as one of media for social change was that thariqah taught the improvement and burdened of individual morals. The research questions were: (1) what is the role of Qadiriyah and Naqsabandiyah thariqahs in people’s spiritual life? (2) what is the role of Qadiriyah and Naqsabandiyah thariqahs in maintaining the people’s social religiosity? The study used field research, namely by digging field data and observing directly. The purpose of this study was to describe the role of Qadiriyah and Naqsabandiyah Thariqah on the people’s social religiosity of Gemutri villagers. The findings revealed that the role of thariqah was to promote spirituality, and to teach noble morals. Increasing spirituality and moral teaching made Gemutri residents as individuals who love each other, do good deeds, be fair, maintain brotherhood, uphold the truth, and help each other. The individual character, according to Abdul Azhim, was the realm of social religiosity.